Gestational age as a predictor for subsequent preterm birth in New South Wales, Australia - Pereira, Gavin; Regan, Annette; Wong, Kingsley; Tessema, Gizachew (BMC, 2021)
Background: There is no validated evidence base on predictive ability and absolute risk of preterm birth by gestational age of the previous pregnancy. Methods: We conducted a retrospective cohort study of mothers who gave birth to their first two children in New South Wales, 1994–2016 (N = 517,558 mothers). For each week of final gestational age of the first birth, we calculated relative and absolute risks of subsequent preterm birth. Results: For mothers whose first birth had a gestational age of 22 to 30 weeks the absolute risks of clinically significant preterm second birth (before 28, 32, and 34 weeks) were all less than 14%. For all gestational ages of the first child the median gestational ages of the second child were all at least 38 weeks. Sensitivity and positive predictive values were all below 30%. Conclusion: Previous gestational age alone is a poor predictor of subsequent risk of preterm birth.